2011
DOI: 10.1007/s13225-011-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of marine mycology

Abstract: Marine fungi have been widely studied over the past millennium and considerable progress has been made in documenting their phylogeny, biodiversity, ultrastructure, ecology, physiology and their ability to cause decay of lignocellulosic compounds. These studies have generated a wealth of publications and this review will focus primarily on research undertaken since 1995. During this period new topics have attracted marine mycologists especially: algicolous and manglicolous fungi, deep sea fungi, planktonic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 372 publications
1
65
0
Order By: Relevance
“…Although marine fungi have been studied for the last 100 years (Jones, 2011), many aspects regarding their taxonomy, ecology and potential biotechnological applications remain poorly documented. Our results are consistent with a suggestion by Bridge and Spooner (2012) that the true diversity of Antarctic fungi may be far greater than is currently estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Although marine fungi have been studied for the last 100 years (Jones, 2011), many aspects regarding their taxonomy, ecology and potential biotechnological applications remain poorly documented. Our results are consistent with a suggestion by Bridge and Spooner (2012) that the true diversity of Antarctic fungi may be far greater than is currently estimated.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of marine fungi has been reported in different substrates such as sponges, algae, wood, tunicates, sediments, mollusks, corals, plants, fish and the ecology and phylogeny of this group were summarized (Jones, 2000;Jones et al, 2009Jones et al, & 2011Jones and Pang, 2012;Richards et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…By 1996, diversity estimates of marine fungi were placed at around 1500 species, and by 2011, estimates projected the number of possible marine fungi as over 10,000 species (Jones, 2011). Marine fungi are considered important ecological components in marine environments due to their performance in biogeochemical processes (Tedersoo et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a quantitative view, marine fungal species represent a tiny fraction of global fungal diversity compared to terrestrial representatives. Indeed, recent reports have suggested that there are only 549 marine fungi, including 439 Ascomycota, 94 mitosporic fungi, and 16 Basidiomycota (Jones, 2011). Hence, only 0.74% of the fungal species described to date are derived from the oceans.…”
Section: Definition and Novel Conceptmentioning
confidence: 99%
“…In littoral regions the fungal species are mainly involved in wood decay, with an ability to cause soft rot and white rot attacks by the synthesis of extracellular cellulose-degrading cellulases and lignin-degrading laccases (Jones, 2011). Wood appeared as a suitable substrate for marine fungi in the oceanic biome; indeed, fungal sporocarps have been detected on wood fragments in the Vanuatu archipelago at depths of between 100 and 1200 m (Dupont et al, 2009).…”
Section: Ecological Rolesmentioning
confidence: 99%